Field electron emission properties of carbon nanotube films deposited by electrophoresis - Nor, R.M. (2011)
The merit of various kinds of carbon nanotubes as field electron emission cathode materials has been studied. The field electron emission characteristics of electrophoretically deposited films of single walled carbon nanotubes, multiwalled carbon nanotubes of diameter between 10 and 20 and >50 nm and carbon nanofibres with diameters between 200 and 600 nm were investigated. Results of the measurements revealed that the field enhancement factor beta, the turn on electric field and the threshold electric field were strongly dependent on the size of carbon materials, where single walled carbon nanotubes produced the best results in terms of lowest electric field values, highest field enhancement factor and highest current density.